Discourses of dementia in the British press: a corpus linguistic approach - Bailey, Annika (2019)
This study investigates discourses of dementia in the British national news media, examining a two million word collection of news articles about dementia published between 2012 and 2017. Using a mixed-methods approach, the study combines the quantitative techniques of corpus linguistics with the qualitative perspectives of Critical Discourse Analysis, a methodological combination that affords a means of identifying the most salient linguistic patterns and trends. In light of the stigma and cultural misunderstanding that popularly surrounds the syndrome, the study seeks to explore how dementia, and those living with dementia, are discursively represented in the British press.